PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN DI PT. PERKEBUNAN NUSANTARA III (PERSERO) - Yusrita . (JRMB (Jurnal Riset Manajemen & Bisnis), 2019)
This study aims to determine the effect of Emotional Intelligence and Spiritual Intelligence on Employee performance at PT. Perkebunan Nusantara III (Persero) Medan. The number of sampling in this study was 30 people. The sample is taken using total sampling where the sampling technique is the same as the population. Data collection techniques used questionnaires, interview, documentation studies, and quantitative method. The resultshowed thet emotional intelligenceshas a positive and significant effect on employee perfomence, a emotional intelligence and Spiritual intelligence simultaneously have a positive and significant effect on emplayee performence.